2021
DOI: 10.1155/2021/7007933
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Ferroptosis‐Related Markers for the Clinical and Biological Value in Gastric Cancer

Abstract: Gastric cancer is a highly malignant tumor with poor survival rate. Ferroptosis, a newly defined regulated cell death, is closely related to several tumors. Introduction of ferroptosis is promising for cancer treatments. However, the predictive role of ferroptosis in GC remains elusive. In this study, we screened the ferroptosis-related genes which were differentially expressed between normal and GC tissues. Then, based on these differentially expressed genes (DEGs), the least absolute shrinkage and selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Similarly, several studies have shown that AIFM2 represents an unfavorable prognostic factor in prostate cancer, acute myeloid leukemia and uveal melanoma (Luo and Ma, 2021;Lv et al, 2021;Song et al, 2021). However, a recent study has indicated that AIFM2 act as a favorable factor for OS of gastric cancer patients, which is consistent with the findings of our study (Shao et al, 2021). Therefore, it is interesting to explore the effect of AIFM2 on the prognosis of different types of tumors.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, several studies have shown that AIFM2 represents an unfavorable prognostic factor in prostate cancer, acute myeloid leukemia and uveal melanoma (Luo and Ma, 2021;Lv et al, 2021;Song et al, 2021). However, a recent study has indicated that AIFM2 act as a favorable factor for OS of gastric cancer patients, which is consistent with the findings of our study (Shao et al, 2021). Therefore, it is interesting to explore the effect of AIFM2 on the prognosis of different types of tumors.…”
Section: Discussionsupporting
confidence: 91%
“…Unexpectedly, low-risk GAC patients had a greater TMB, suggesting that low-risk patients may be more likely to benefit from immunotherapy. This result is consistent with the findings of Shao et al (2021 ). Among the common ICPs, however, only the expression of PDL2 was significantly higher in the high-risk group.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the studies on the relationship of iron and GC, ferroptosis has also been found to be closely related to the proliferation, invasion, and metastasis in GC ( Chen et al, 2021a ; Huang et al, 2021 ). However, the predictive role of ferroptosis in GC remains elusive ( Shao et al, 2021 ). Thus, understanding the processes underlying ferroptosis is promising for the development of cancer treatment strategies.…”
Section: Ferroptosis In Gastric Cancermentioning
confidence: 99%
“…Biomarkers for the characterization of the tumor immune microenvironment may add to the predictive value of the current staging system ( Jiang et al, 2019 ). In recent decades, large-scale clinical trans-omics studies allowed the identification of some crucial ferroptosis-related genes as reliable biomarkers to describe the tumor immune microenvironment landscape and predict response to antitumor therapy ( Liu S. J. et al, 2021 ; Shao et al, 2021 ).…”
Section: Tumor Microenvironment In Gastric Cancermentioning
confidence: 99%